Anxiety and Depression in Patients With Vestibular Disorders - Bao Y. Sciscent; Marc Polanik; F. Jeffrey Lorenz; Hänel W. Eberly; Mark E. Whitaker (OTO Open, 2025)
Abstract Objective To investigate the prevalence of depression and anxiety in patients with vestibular disorders using a large patient database. Study Design Retrospective cohort. Setting The TriNetX database. Methods TriNetX, a deidentified database, was retrospectively queried to identify adults with vestibular disorders. The rates of anxiety and depression in patients with vestibular disorders were compared to patients without vestibular disorders within 5 years of the index event, which was set at the time of diagnosis of vestibular dysfunction. Results On analysis of patients with and without vestibular disorders, after propensity score matching for demographics and common comorbidities, 64,153 patients were identified in each cohort. Patients with vestibular disorders were more likely to have depression (relative risk [RR] 1.37 [95% CI 1.35‐1.40]) and anxiety (RR 1.51 [95% CI 1.45‐1.57]) compared to the general population. Similarly, a higher rate of antidepressant use was seen in patients with vestibular disorders (RR 1.41 [95% CI 1.39‐1.43]). Conclusion Patients with vestibular disorders have higher rates of depression and anxiety compared to the general population.